Pengurusan Air Pahang Berhad Daerah Maran / Nur Hasanah Mohd Zubaidi - Mohd Zubaidi, Nur Hasanah (Faculty Of Chemical Engineering, 2021)
A lot of unexpected things happened that have experienced and faced in order to complete the diploma, it is such a bitter-sweet memories. The real working industry is not as easy as a piece of cake thing to deal with it where any little wrong step, will definitely turn it into a mess. This course thought to always have backup plan and always think outside the box. Expect the unexpected, prepare for any circumstances that may happen in the future. It was so grateful for having this opportunity in experiencing both industrial working and work from-home style of working, it was completely different experience with other batch for have done internship before that not experience work from home style. Although work from home style is quite similar with open distance learning in university, it faced the real process and condition in real working that need wide problem solution. It such a good process of learning for preparing in the future. If there are another opportunity of industrial training, it is a better choice for choosing 'hands-on' industrial training because it gives more exposure and practice of the real working life of engineer on reality of chemical engineering. However, it was a great experience overall. Last but not least, environmental issues are very important to be taken care of and have to be taken seriously. All the industries that produce wastewater have to treat their waste in a proper way to sustain the environment for the future generation.